2012
DOI: 10.1088/0964-1726/22/1/015013
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistive behavior and multi-directional strain sensing ability of carbon nanotube–graphene nanoplatelet hybrid sheets

Abstract: Free-standing carbon nanomaterial hybrid sheets, consisting of multi-walled carbon nanotubes (MWCNTs), exfoliated graphite nanoplatelets (xGnPs) and nanographene platelets (NGPs) of different lengths and lateral dimensions, have been prepared using various material combinations and compositions. When subjected to tensile strains, the carbon nanomaterial sheets showed piezoresistive behavior, characterized by a change in electrical resistance with applied strain. Simultaneous measurement of resistance changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 24 publications
(26 reference statements)
1
43
0
Order By: Relevance
“…It was postulated that GnP would demonstrate quality similar to graphene owing to its much pristine basal plane configuration in comparison to GO [57]. GnP has been shown to bring tremendous improvement in diverse applications due to its extremely high optical, electrical, thermal, and mechanical as well as piezoresistive properties [58,[61][62][63][64][65]. The defect on GnP edges which mostly consists of unfilled trigonal carbon bonds promotes favorable site for oxidative reaction with ambient gas to yield more hydrophilic structure which comprises various water-based functional groups (i.e., ethers, carboxyls, or hydroxyls) [51,58].…”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that GnP would demonstrate quality similar to graphene owing to its much pristine basal plane configuration in comparison to GO [57]. GnP has been shown to bring tremendous improvement in diverse applications due to its extremely high optical, electrical, thermal, and mechanical as well as piezoresistive properties [58,[61][62][63][64][65]. The defect on GnP edges which mostly consists of unfilled trigonal carbon bonds promotes favorable site for oxidative reaction with ambient gas to yield more hydrophilic structure which comprises various water-based functional groups (i.e., ethers, carboxyls, or hydroxyls) [51,58].…”
Section: Introductionmentioning
confidence: 99%
“…However, 1D nanomaterials-based systems could achieve extremely high stretchability but often exhibit poor sensitivity (GF < 10). 20 −24 In this context, binary systems of 0D and 1D has been explored, including CNTs/AgNPs, 30 CNTs/graphene, 31,32 and AgNWs/ AgNPs. 33 It was reported that the sensitivity could increase more than 23 times when silver NPs were added into CNTs; 30 the conductivity could increase more than 1 × 10 6 times when AgNPs were added into AgNWs.…”
mentioning
confidence: 99%
“…Literature [134][135][136][137][138][139][140][141] depicted that 10 fold increases in the ZT was observed by the addition of 2-3 wt% of graphene. This value is much higher than that of CNT based composites.…”
Section: Pedot:pss-graphene Filled Compositementioning
confidence: 99%